Nurse Resilience in The Covid-19 Pandemic at Palang Merah Indonesia, Bogor Hospital - Fachturohman, Mochamad Arfan; Adhikara, MF Arrozi; Wahidi, Kemala Rita (Alta Dharma Publisher, 2022)
Introduction: The nurse's performance was successful in carrying out the task and achieving the stated goals. The performance can be declared excellent and successful if the desired goals can be appropriately performed. Method: The design of this study was a correlational quantitative analytic study with a cross-sectional study design. The analysis technique used structural equation modeling. The sampling technique used probability sampling, namely disproportionate stratified. Measurements in this study used a questionnaire distributed to 210 respondents and a questionnaire that returned several 210 sets of questionnaires. Results: The results showed that quality of work-life, role conflict and work stress were influence to nurse performance; quality of work-life was an influence to work stress; role conflict was an influence to job stress; job stress was an influence to nurse performance; quality of work-life was an influence to nurse performance, and role conflict was an influence to nurse performance. Recommendation: The research implication for management has to improve the nurses’ performance by increasing the quality of work-life and controlling role conflict and work stress so that performance results become better and support achievement.